Deixis in Egyptian : The Close, the Distant, and the Known - Kupreyev, Maxim N. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
In this volume, Maxim N. Kupreyev explores the intricate stories of Egyptian-Coptic demonstratives and adverbs, personal, relative pronouns and definite articles. Applying the concepts of distance, contrast, and joint attention, the book offers a panorama of competing deictic systems in Old Kingdom Egypt. It singles out dialectal differences and outlines the history of deixis not as a linear development, but as a competition of regional variants that gradually attain normative status. The results of the study reconsider the evolution of Ancient Egyptian, its periodization and its embedding in the Afro-Asiatic linguistic context.